Adriana Bolívar. Political Discourse as Dialogue. A Latin American Perspective. London and New York: Routledge. 209 pp. ISBN: 978-1-138-67878-1 (hbk) ISBN: 978-1-315-55870-7 (ebk) - Fadda, Sandra (Discurso & Sociedad, 2018)
Adriana Bolívar. Political Discourse as Dialogue. A Latin American Perspective. London and New York: Routledge. 209 pp. ISBN: 978-1-138-67878-1 (hbk) ISBN: 978-1-315-55870-7 (ebk).